Quelle base factuelle pour une stratégie européenne de développement durable dans les régions de montagne ? - Erik Gløersen; Clemens Mader; Engelbert Ruoss (Revue de Géographie Alpine)
The aspiration to implement evidence-based policies has led to an increased focus on quantitative indicators and targets defined at the European level as instruments for designing policy measures and assessing their impact. The authors argue that this constrains debate and has hindered the elaboration of a proactive European strategy for sustainable development in mountain regions. Mountain territories have highly diverse social, economic and physical characteristics; their shared traits in terms of ecological fragility, economic development challenges and exposure to natural hazards are not reflected in mainstream datasets. Two complementary instruments are proposed to produce and present evidence for sustainable resource management and processes: the Nexus Model and the Sustainability Profile Matrix. Both tools entail using evidence that is adapted to the social and economic characteristics, potentials and challenges of each locality or region. At the same time, they make compilations of evidence at the transnational and European levels possible. The objective is to enable local, national and transnational authorities to use territorial diversity as a lever in their policies, within multilevel governance in human, economic and natural resource management.